People who own themselves : aboriginal ethnogenesis in a Canadian family, 1660-1900 - Devine, Heather (University of Calgary Press ; Gazelle, 2004)
With a unique how-to appendix for Metis genealogical reconstruction, this book will be of interest to Metis wanting to research their own genealogy and to scholars engaged in the reconstruction of Metis ethnic identity. The search for a Metis identity and what constitutes that identity is a key issue facing many aboriginals of mixed ancestry today. This book reconstructs 250 years of the Desjarlais' family history across a substantial area of North America, from colonial Louisiana, the St. Louis, Missouri, region and the American Southwest to the Red River and central Alberta. In the course of tracing the Desjarlais family, social, economic and political factors influencing the development of various Aboriginal ethnic identities are discussed. With intriguing details about the Desjarlais family members, this book offers new, original insights into the 1885 Northwest Rebellion, focusing on kinship as a motivating factor in the outcome of events.